Same reason, same right? The constitutional guardianship of the national investor for indirect expropiations - López Flores, Luciano (2020)
This essay deals with the thesis of the protection of indirect expropriations of national investors, invoking the equal treatment —with the advantages, rights and guarantees of the foreign investor— established in article 63 of the Peruvian Constitution. Our goal is to make explicit the reasons why is it now possible to go forward in the procedural protection of the national investor against cases of indirect expropriation, by using arbitration instead of the amparo process for that purpose. This other procedural protection derives from the Bilateral Investment Treaties and Free Trade Agreements that provides for national or international investment arbitration. Given that this arbitration procedure arises from a legal source, the national investor, under the principle of equality of treatment of the foreign investor is also entitled to use it.